THE ANALYSIS OF EFFECTIVENESS OF USING DRONE EMPRIT AS A CYBER PATROL ASSISTANCE TOOL: LAMPUNG AND NORTH SUMATRA REGIONAL ELECTION STUDY CASE - Pebriandi Haloho; Surya Nita; Muhammad Erza Aminanto (Transpublika Publisher, 2024)
This study evaluates the effectiveness of Drone Emprit as a cyber patrol tool during the 2024 regional elections (Pilkada) in Lampung and North Sumatra. By leveraging big data analytics and natural language processing, Drone Emprit monitors public sentiment and key issues on social media, such as neutrality of civil servants (ASN), misinformation, and potential conflicts. Using a mixed-method approach, data were collected from Twitter over four observation periods. The findings show significant changes in public sentiment, with positivity dominating early periods and negativity increasing in later periods due to controversies. The analysis highlights Drone Emprit real-time capabilities in detecting public sentiment, identifying key issues, and supporting strategic decision-making. This study underscores the potential of big data tools to enhance cyber patrols and maintain social stability during politically sensitive periods.